The cowboy's English lady - Robinson, Lauri (Harlequin historicals., 2025)
"When rancher Jake Simpson hears of his philandering cousin's upcoming marriage to Lady Caroline Evans, he can't let it happen: the good-for-nothing groom's bound to someone else! But storming to London and stopping the wedding leaves Lady Caroline in need of a husband ... Honor bound to save her reputation, Jake offers himself--and a ticket to accompany him back to Texas, where gossip can't hurt her. It's supposed to be an arrangement of strict convenience, but Jake didn't count on finding Caroline's sweetness quite so charming. Soon he finds himself wondering whether this rugged cowboy can win his refined English wife's heart ..."--